2019
DOI: 10.18203/2394-6040.ijcmph20195177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression, anxiety and stress among school going adolescents in Delhi: a cross sectional study

Abstract: Background: Adolescence is a stressful period due to physical, psychological, sexual changes and the presence of psychiatric disorders such as depression, anxiety and stress at this stage of life is a matter of concern. Depression is a common mental disorder, characterized by persistent sadness and a loss of interest in activities that you normally enjoy, accompanied by an inability to carry out daily activities, for at least two weeks. The objective of this study is to find the prevalence and associated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
3
17
4
Order By: Relevance
“…In the neighboring countries like India, the age-adjusted prevalence of anxiety among rural adolescents was 16.6%, which is much lower than that of the current study [33]. In another study, conducted upon school adolescents in Delhi, the prevalence of anxiety was 65.3%, which is much higher than that of the present study [34]. The difference in the prevalence of anxiety reported in these studies might be attributed to the demographic setting, since the first one was conducted upon rural adolescents, while the later upon urban adolescents.…”
Section: Plos Onecontrasting
confidence: 85%
“…In the neighboring countries like India, the age-adjusted prevalence of anxiety among rural adolescents was 16.6%, which is much lower than that of the current study [33]. In another study, conducted upon school adolescents in Delhi, the prevalence of anxiety was 65.3%, which is much higher than that of the present study [34]. The difference in the prevalence of anxiety reported in these studies might be attributed to the demographic setting, since the first one was conducted upon rural adolescents, while the later upon urban adolescents.…”
Section: Plos Onecontrasting
confidence: 85%
“…While some existing community-based studies have found that adolescent depression is largely of mild (Grover et al, 2019 ; Lodha et al, 2016 ) or moderate severity (Kumar et al, 2019 ; Malik et al, 2015 ), this study found that the symptomatic percentages of mild (= 18%), moderate (= 17.5%), and severe (= 16.3%) categories were almost comparable. The increased intensity of depression may be explained by the fact that this study was conducted almost 8 months into the lockdown, during which time youth had been in a state of prolonged social disconnect.…”
Section: Discussioncontrasting
confidence: 65%
“…The NMHS survey ( 2016 ), one of the most elaborate and detailed analyses of mental health indicators of the Indian population based on information from 12 geographically and culturally diverse states, found a point prevalence rate of 2.6% for depressive disorders among youth. Independent studies from different states have found much higher prevalence rates ranging from 40% in Chandigarh, 47.9% in New Delhi, and 49.2% in Patna, Bihar, to 52.9% in Rohtak, Haryana, and 71.3% in Bhopal (Madhya Pradesh) (Kumar et al, 2019 ; Malik et al, 2015 ; Singh et al, 2017 ). Similar variations were seen in studies from South India as well, with prevalence rates ranging from 39% in rural Karnataka and 43% in North Kerala to 57.6% in urban Mangalore (Shaikh et al, 2018 ; Hanspal et al, 2019 ; Pandian et al, 2017 ; Shelke et al, 2015 ; Urmila et al, 2017 ).…”
mentioning
confidence: 99%
“…[ 16 ] from Chandigarh, north India (40%); Kumar et al . [ 17 ] from Delhi, north India (47.9%); Sandal et al . [ 18 ] from Chandigarh, north India (65.53%); Malik et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] from Pariyaram, Kerala, south India (57.7%); Kumar et al . [ 17 ] from Delhi, north India (47.9%); and Nagendra et al . [ 12 ] from Davangere south India 57.7%.…”
Section: Discussionmentioning
confidence: 99%